RETRACTED: Coping stress toward post-death of a couple: A qualitative study in single mothers - Sairah (INSPIRA: Indonesian Journal of Psychological Research, 2021)
This article has been retracted: please see INSPIRA: Indonesian Journal of Psychological Research Retraction, Withdrawal, & Correction (R-W-C) Policy (https://journal.iainlangsa.ac.id/index.php/inspira/rwc-policy). This article has been retracted at the request of the Editorial-in-Chief. The editor detected the article as a dual submission due to the similarity with:Hafni, M. & Sairah (2021). Coping stress post-mortal spouse: A qualitative study of single mothers. International Journal of Management Studies and Social Science Research, 3(2), 173-180. https://www.ijmsssr.org/paper/IJMSSSR00373.pdf